Power Relations and Rural Population in Kuban-Black Sea Region during 1921—1924 - A. V. Baranov; V. V. Kasyanov; Yu. A. Yakhutl (Научный диалог, 2023)
The article examines the reforms in power relations between the government and rural population in the Kuban-Black Sea region during the transition to the New Economic Policy (March 1921—1924). The study is based on materials from party and state authorities, as well as statistics. A systemic approach and diachronic comparative analysis are applied. The authors argue that until the fall of 1922, the system of power relations with the rural population in Kuban-Black Sea region maintained the predominance of the features of “war communism”: compulsory and arbitrary taxation, appointment of governing bodies, and repression. The specificity of the region was manifested in the combination of class and estate divisions of society, as well as Cossackization. It is shown that the transition to the NEP required a fundamental change in power relations with the peasantry, shifting towards the principles of material interest and civil peace, making the middle class and Cossacks loyal. It is emphasized that attitudes towards the NEP were contradictory, with local party and Soviet workers preferring to rely on military-communist methods. The authors conclude that a contradictory system of power and social relations was formed based on compromises and indirect coercion during food and land policies and during elections to the Soviets. By the fall of 1924, the RCP(b) was forced to concede to peasant demands on key aspects of reform.